Hemicellulases and acessory proteins from filamentous fungi and actinomycetes for lignocellulose biomass deconstruction. - Robl, Diogo (2015)
Endophytic microorganisms were screened for hemicellulases production using plate assays and liquid cultivations. Two strains were selected and used in further studies. Aspergillus niger DR02 strain and Annulohypoxylon stigyum DR47. In A.niger fed-batch submerged cultivation approaches were developed using liquor from hydrothermal sugar cane pretreatment, and maximum xylanase activities obtained were 458.1 U/mL for constant fed-batch mode. For A. stygium DR47 media optimization and bioreactor cultivation using citrus bagasse and soybean bran were explored and revealed a maximum production of 6.26 U/mL of pectinase and 10.13 U/mL of β-glucosidase. Improved hemicellulase production was also done by genetic modifications at carbon catabolic repression levels in A. niger. Mass spectrometric studies were done in enzymatic extracts produced and contributed to understand the enzymatic supplementation of Celluclast 1.5L.In addition the extracts produced were tested for an enzyme formulation and that was able to increase sugar cane bagasse hydrolysis.